Penerapan Permainan Kecil untuk Meningkatkan Motivasi Belajar Pjok pada Siswa Kelas VI SDS Nahdatul Ulama 10 Medan - Aissyahkila Nazwa Dalimunthe; Abelia Abelia; Marisha Rahmani Tanjung (Mathematics Education Study Program, 2025)
The research conducted by the author was motivated by the low learning motivation of fourth grade students of SDS Nahdatul Ulama Medan in PJOK learning. The purpose of this study was to determine whether the application of small games can increase the learning motivation of PJOK class VI students of SDS Nahdatul Ulama Medan.This type of research is class action research (PTK).The stages carried out in class action research are as follows: develop a plan (plan), take action (act), conduct observation (observe), reflect (reflect). The subjects in this study amounted to 20 fourth grade students. This research was conducted in two stages of meetings. The results of this study indicate an increase in student learning outcomes obtained from observation sheets conducted after stages I and II with the action of applying small games.